2011
DOI: 10.19030/iber.v6i6.3377
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Applications Of Weather Derivatives

Abstract: Weather derivatives are currently a fast growing derivatives sector. The purpose of this article is to examine the background of the weather derivatives market and some of its benefits for agricultural risk management. In addition, this article is meant to serve as an overview of the benefits and uses of weather derivatives for those who may not be otherwise exposed to this type of market. This article examines the structure of Heating Degree Day and Cooling Degree Day contracts along with agricultural hedging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…He has suggested to take up the further research to frame the effective rainfall risk hedging contracts and develop widely acceptable pricing model. Travis (2007) concluded that weather futures can be easily used to hedge agricultural volumetric risk and it leads to increase the revenue to the farmers and other agri-businesses. Barry et al (2008) suggested that index-based rainfall risk transfer products were valuable instruments for addressing the problem of crop insurance failure.…”
Section: Review Of Literaturementioning
confidence: 99%
“…He has suggested to take up the further research to frame the effective rainfall risk hedging contracts and develop widely acceptable pricing model. Travis (2007) concluded that weather futures can be easily used to hedge agricultural volumetric risk and it leads to increase the revenue to the farmers and other agri-businesses. Barry et al (2008) suggested that index-based rainfall risk transfer products were valuable instruments for addressing the problem of crop insurance failure.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The momentum for creating weather derivatives were deregulation of the energy and utility industries in USA in mid-1990s [23] and extremely worm El Nino winter 1997/1998 in USA [24]. With deregulation, monopolies began to be replaced with competitive market structures and many energy and utility companies learned that while they could hedge away price risk with futures and options on energy itself, they had no instrument to hedge away weather risk that could dramatically alter the demand for or production of their products.…”
Section: Weather Derivatives As a Risk Management Tool In Energy Sectormentioning
confidence: 99%
“…The major participants in the weather derivatives market include energy companies, insurance and reinsurance companies, market markers, brokers and other retail participants like agriculture, transport, entertainment and tourism firms [23]. Currently, weather derivatives contracts are listed in major derivatives exchanges like Chicago Mercantile Exchange (CME) for various cities in America, Europe and Asia [25].…”
Section: Introduction 1general Introductionmentioning
confidence: 99%